2015
DOI: 10.2527/jas.2014-8419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium and vitamin E on performance, physiological response, and selenium balance in heat-stressed sheep1

Abstract: Forty-two 7-mo-old Australian Merino wethers were used in a 50-d trial to investigate the effects of Se and vitamin E on the performance and physiological responses of heat-stressed sheep. Sheep were exposed to thermoneutral conditions (maximum = 24°C and minimum = 20°C) for 28 d followed by heat (maximum = 38°C and minimum = 28°C) for 22 d. Hot conditions were imposed between 0700 and 1800 h. Sheep were randomly allocated to diets containing 0.8 mg/kg Se (Sel-Plex), 150 mg/kg vitamin E, or 0.8 mg/kg Se and 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
2
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 58 publications
7
15
2
3
Order By: Relevance
“…Likewise, no effect of Vit. E and Se was observed in previous studies (Tahmasbi et al, 2012;Alhidary et al, 2015) during summer. The increase in testosterone in response to Se (Shi et al, 2018) and Vit.…”
Section: Discussionsupporting
confidence: 68%
“…Likewise, no effect of Vit. E and Se was observed in previous studies (Tahmasbi et al, 2012;Alhidary et al, 2015) during summer. The increase in testosterone in response to Se (Shi et al, 2018) and Vit.…”
Section: Discussionsupporting
confidence: 68%
“…In contrast with α-tocopherol, Se concentration in serum was unaffected by AOX supplementation. Some studies have reported increased serum concentrations of Se in sheep in response to dietary supplementation of inorganic Se, with levels of sodium selenite supplementation similar to (Kumar et al, 2008) or greater than (Davis et al, 2008;Alhidary et al, 2015) that used in the current study. Nevertheless, in agreement with our study, Cristaldi et al (2005) did not observe changes in serum Se concentration in wether lambs fed diets with either 0.2 or 2 mg of Se (as selenite)/kg after 16 wk of supplementation.…”
Section: Plasma Concentrations Of α-Tocopherol and Sementioning
confidence: 75%
“…Selenium is an indispensable component of the antioxidant system; for instance, Se can be used to synthesize glutathione peroxidase (GSH-Px; Rotruck et al, 1973). Thus, conditions that limit Se supply (e.g., decreased feed intake, feedstuff Se deficiency) or that increase Se depletion (e.g., peak lactation) might limit antioxidant capacity (Alhidary et al, 2015). Further, situations where free radical production is exacerbated (e.g., stress, disease) might increase Se requirements.…”
Section: Introductionmentioning
confidence: 99%